‘To Hell with Bishops’: Rethinking the Nexus of State, Law and Religion in Times of Crisis in Zimbabwe - Dube, Bekithemba (Religions, 2021)
The article addresses the responses of the government of Zimbabwe and its proxies to a letter issued by Catholic bishops on 14 August 2020, entitled ‘The march is not ended’. The response to the letter presents an ambivalent view of the nexus of the state, law and religion in Zimbabwe, which needs to be teased out and challenged in order to reinvent a democratic nation. This theoretical article taps into decoloniality theory to problematise state responses to the letter. The articles discuss responses by government actors, such as Monica Mutswanga and Nick Magwana, and regime enablers, such as Mutendi and Wutawunashe. The responses indicate the weaponization of religion and law to silence dissenting voices, and to enact a skewed nationalism. The article argues that, in the context of crisis, authoritarianism, and abuse of human rights, politicians and religious leaders should position their narratives to enact social justice, ontological density, peace and accountability, as a healing process to usher in sustainable development.